Mass Spectrometry–Based Adrenal and Peripheral Venous Steroid Profiling for Subtyping Primary Aldosteronism. (6th January 2020) - Eisenhofer, Graeme; Dekkers, Tanja; Peitzsch, Mirko; Dietz, Anna S; Bidlingmaier, Martin; Treitl, Marcus; Williams, Tracy A; Bornstein, Stefan R; Haase, Matthias; Rump, L C; Willenberg, Holger S; Beuschlein, Felix; et al.
Abstract: BACKGROUND: Differentiating patients with primary aldosteronism caused by aldosterone-producing adenomas (APAs) from those with bilateral adrenal hyperplasia (BAH), which is essential for choice of therapeutic intervention, relies on adrenal venous sampling (AVS)-based measurements of aldosterone and cortisol. We assessed the utility of LC-MS/MS–based steroid profiling to stratify patients with primary aldosteronism. METHODS: Fifteen adrenal steroids were measured by LC-MS/MS in peripheral and adrenal venous plasma from AVS studies for 216 patients with primary aldosteronism at 3 tertiary referral centers. Ninety patients were diagnosed with BAH and 126 with APAs on the basis of immunoassay-derived adrenal venous aldosterone lateralization ratios. RESULTS: Among 119 patients confirmed to have APAs at follow-up, LC-MS/MS–derived lateralization ratios of aldosterone normalized to cortisol, dehydroepiandrosterone, and androstenedione were all higher ( P < 0.0001) than immunoassay-derived ratios. The hybrid steroids, 18-oxocortisol and 18-hydroxycortisol, also showed lateralized secretion in 76% and 35% of patients with APAs. Adrenal venous concentrations of glucocorticoids and androgens were bilaterally higher in patients with BAH than in those with APAs. Consequently, peripheral plasma concentrations of 18-oxocortisol were 8.5-fold higher, whereas concentrations of cortisol, corticosterone, and dehydroepiandrosterone were lower in patients with APAs than in those with BAH. Correct classification of 80% of cases of APAs vs BAH was thereby possible by use of a combination of steroids in peripheral plasma. CONCLUSIONS: LC-MS/MS–based steroid profiling during AVS achieves higher aldosterone lateralization ratios in patients with APAs than immunoassay. LC-MS/MS also enables multiple measures for discriminating unilateral from bilateral aldosterone excess, with potential use of peripheral plasma for subtype classification.